A One-Pot Approach for the Preparation of Novel Anil-Like Compounds from 2,3-Dihydroxynaphthalene - Sadeghpour, Mahdieh; Mohammadgoliha, Mahbubeh (Letters in Organic Chemistry, 2017)
Background: A series of novel anil-like compounds was constructed via a three-component domino condensation of 2,3-dihydroxynaphthalene, triethylorthoformate and heteroaryl amines in the presence of formic acid catalyst under solvent-free conditions. Significant features of this method are: simplicity of the procedure, clean reaction, short reaction time, the ready accessibility, and cost effectiveness of the catalyst, high yields, easy work-up and purification of novel products by non-chromatographic methods. Methods: Initially, the three-component condensation reaction of 2,3-dihydroxynaphthalene, 2- aminopyrimidine, and triethylorthoformate as a model reaction was performed at a temperature of 80- 150oC in the presence of formic acid as catalyst (10 mol%) without the use of solvent. We were pleased to find that the reaction proceeded smoothly and almost complete conversion of reactants was observed at 110oC to afford the desired product in 87% yield after running the reaction for 20 min. We also varied the amount of formic acid for this condensation. To our delight, the reaction worked very well in the formic acid as catalyst (10 mol%) at 110oC under solvent-free conditions. Results: After optimizing the conditions, we turned to explore the scope of the reaction using different heteroaryl amines, 2,3-dihydroxynaphthalene and triethylorthoformate under the optimized reaction conditions for the synthesis of novel anil-like compounds. It was found that, various heteroaryl amines containing electron-donating or electron-withdrawing functional groups at different positions showed almost the same yields. It is very important to mention here that according to the 1H NMR and 13C NMR spectra, these Schiff bases favor the keto-enamine form over the enol-imine form which is also in agreement with strong intramolecular hydrogen bond (O…H-N). Conclusion: We described a convenient, efficient, and environmentally greener methodology for the synthesis of novel anile-like compounds (Schiff bases) in the presence of formic acid catalyst under solvent- free conditions. The present method has advantages, such as omitting organic solvent, simplicity, generality, cleanliness, shorter reaction time, easy work-up and purification of novel products by nonchromatographic methods.
Keywords: 3-Dihydroxynaphthalene